Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Menggunakan Media Fun Mind Mapping terhadap Hasil Belajar IPS Siswa Kelas VIII UPT SMP Negeri 3 Srengat - Rizqi Anggun Kharisma; Nur Isroatul Khusna (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
As an effort to improve the learning process, this study aims to describe the effect of the Contextual Teaching and Learning (CTL) learning model with Fun Mind Mapping media on learning outcomes (cognitive, affective, psychomotor). The approach used in this research is a quantitative approach. The type of research used is a type of experimental research. The population in this study were all students of class VIII UPT SMP Negeri 3 Srengat. The sampling technique used was purposive sampling. The instruments used to measure learning outcomes are test questions and questionnaires. The data analysis technique used in this study is the data instrument test with the validity test and reliability test, the prerequisite test with the normality test and homogeneity test, and the hypothesis test with the t-test. The results showed that partially there was an influence of the Contextual Teaching and Learning (CTL) learning model with Fun Mind Mapping media on students' cognitive, affective, and psychomotor learning outcomes. This is evidenced by the results of data analysis with the help of SPSS 22 for windows on cognitive aspects 0.017 <0.05, affective aspects 0.046 <0.05, and psychomotor aspects 0.048 <0.05, which means H0 is rejected and H1 is accepted.